Tell el-Retaba 2012: the pottery - Anna Wodzińska (Polish Archaeology in the Mediterranean, 2016)
Archaeological remains excavated by the Polish–Slovak Archaeological Mission in Tellel-Retaba can be well dated to the New Kingdom till the Late Period. During the 2012 seasondomestic layers from the Hyksos period were found, indicating that the site was occupied for thefirst time around the end of the Thirteenth and beginning of the Fifteenth Dynasties. Next to thehouses three Hyksos graves were found. Archaeological work also revealed houses from the earlyEighteenth Dynasty located just above the Hyksos structures in Area 7. Very interesting materialcame from the late Twentieth Dynasty and Third Intermediate Period houses excavated in Area 9.Rich pottery assemblages mostly of domestic character have been recovered from all of the structures.